CFD simulation of the airflow uniformity in the plant factory. Issue 1 (August 2020) - Fan, Ruiqi; Liu, Huan; Zhou, Shenghan; He, Zhongqun; Zhang, Xin; Liu, Ke; Wang, Jinxiao; Yang, Qichang; Zheng, Yangxia; Lu, Wei
Abstract: The growth of horticultural crops is directly affected by the airflow environment in plant factories. In this experiment, a three-dimensional model was established for an indoor artificial light plant factory using computational fluid dynamics (CFD) to simulate the airflow field distribution in the plant factory, the measured value and the simulated value of air velocity were in good agreement, only 10% of the cultivation area was in the range of suitable growth air velocity. The optimization design of airflow field in the plant factory will be developed.